The role of tumor-associated macrophages in breast cancer - Irianiwati, Irianiwati (Universitas Gadjah Mada, 2011)
Interaction of Tumor-Associated Macrophages (TAMs) with tumor cells gives insights into tumor progression andinto a novel therapeutic strategy. In papillary thyroid cancer, patients with tumors containing TAMs had a betterprognosis than patients without TAMs . In prostatic cancer, the reduced of total TAMs can be used as a novelprognostic marker. In melanoma maligna, high number of TAMs was statistically significant associated with poorresponse to treatment . In breast cancer progression, the role of TAMs is still unclear.Key words: tumor-associated macrophages - breast cancer â angiogenesis - tumor progression - prognosis